2022
DOI: 10.1111/ecc.13625
|View full text |Cite
|
Sign up to set email alerts
|

Intensive complex physical therapy combined with intermittent pneumatic compression versus Kinesio taping for treating breast cancer‐related lymphedema of the upper limb: A randomised cross‐over clinical trial

Abstract: Objective: The objective of this study is to compare the effectiveness of complex physical therapy combined with intermittent pneumatic compression (CPT + IPC) versus Kinesio taping (KT) for breast cancer-related lymphedema. Methods: A cross-over clinical trial was conducted in 43 women with lymphedema. All participants received two interventions: CPT + IPC and KT, both lasting 3 weeks and a washout period. The main outcome variable was the relative volume change (RVC). The secondary variables were Satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Nevertheless, Pajero-Otero et al showed in a recent cross-over trial that KT was more satisfactory than multilayer bandaging, obtaining better DASH scores compared with CPT + IPC. 70 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Pajero-Otero et al showed in a recent cross-over trial that KT was more satisfactory than multilayer bandaging, obtaining better DASH scores compared with CPT + IPC. 70 …”
Section: Discussionmentioning
confidence: 99%
“…As is the case with the PNF method, few publications examine the relationship between KT and cancer, and the existing ones focus primarily on oedema in women with breast cancer [31,32]. Only Otero et al [20] in their next work, in addition to the positive impact of KT on, for example, the range of motion and oedema, showed that this method was more effective in reducing pain than other physiotherapeutic methods in women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CDT, other measures such as intermittent pneumatic compression therapy (IPCT) are available. IPCT is an approved [ 15 , 16 , 17 , 18 , 19 ] therapy (especially in inpatient settings [ 20 ]) that, despite its potential as a home and continuous therapy, seems to be less established. There is an unsatisfactory situation in the study of the therapy of chronic lymphedema in general, and in manual lymphatic drainage and intermittent pneumatic compression in particular [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%